2009
DOI: 10.1038/mt.2009.51
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Enhancers Induce Insertional Gene Deregulation Independently From the Vector Type and Design

Abstract: The integration characteristics of retroviral (RV) vectors increase the probability of interfering with the regulation of cellular genes, and account for a tangible risk of insertional mutagenesis in treated patients. To assess the potential genotoxic risk of conventional or self-inactivating (SIN) gamma-RV and lentiviral (LV) vectors independently from the biological consequences of the insertion event, we developed a quantitative assay based on real-time reverse transcriptase--PCR on low-density arrays to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 23 publications
2
62
2
Order By: Relevance
“…Extensive studies have shown that the enhancer sequences are the major cause of cell transformation, making the design of viral vectors for life-long therapy approaches even more challenging. [8][9][10] Insulators mark the boundaries of chromatin domains and limit the range of action of enhancers and silencers. 11 They are characterized by at least one of the following properties: Enhancer blocking and/or boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that the enhancer sequences are the major cause of cell transformation, making the design of viral vectors for life-long therapy approaches even more challenging. [8][9][10] Insulators mark the boundaries of chromatin domains and limit the range of action of enhancers and silencers. 11 They are characterized by at least one of the following properties: Enhancer blocking and/or boundary.…”
Section: Introductionmentioning
confidence: 99%
“…The strong transcriptional enhancer present in the MLV long terminal repeat (LTR) played a major role in deregulating gene expression. Preclinical studies showed that enhancer-less (self-inactivating [SIN]), HIV-derived LVs are less likely to cause insertional tumors than MLV-derived vectors (17)(18)(19)(20). Transcriptional gene activation, however, is not the only genotoxic event that may result from retroviral vector integration.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HIV-1 disfavors CpG islands and does not show any preference for TFBSs (16,22,26). Interestingly, integrated lentiviral vectors can both up-and down-regulate host gene expression, in contrast to MLV (20). Another lentivirus, simian immunodeficiency virus (SIV), also shows a similar integration pattern of favoring actively transcribed genes with no preference for TSSs and CpG islands (19,28,29).…”
Section: Lentiviral Integration Into Actively Transcribed Genesmentioning
confidence: 94%
“…Activated oncogenes often turn normal cells into can-cerous cells by perturbing the regulation of cell growth and survival. The retroviral promoter and enhancer components have recently been shown to affect cellular transcription over a long range, independent of vector type, thereby increasing the tumorigenicity of the viral vector (20). The retroviral propensity for frequently targeting oncogenes and cell growth/survival genes and the integration preference for TSSs and CpG islands synergistically increase the malignant potential of retroviral vectors (21).…”
Section: Retroviral Integration Preferences For Genomic Regions Rich mentioning
confidence: 99%